(STAD VS KONVENSIONAL) DAN MODALITAS BELAJAR TERHADAP HASIL BELAJAR GRAMMAR - Imam Mudofir (SENTIA 2016, 2016)
The aim of this study is to examine (1) the differences grammar in English speaking learning outcome taught by Student Teams Achievement Division (STAD) and the conventional learning strategies, (2) student differences grammar in English speaking learning outcome that have different learning modalities (visual, auditory, kinesthetic) gain different result in English speaking skill grammar, and (3) the interaction effect between learning strategies and learning modalities (visual, auditory, kinesthetic) towards grammar in English speaking learning outcome. This research was conducted in the second semester of academic year 2015-2016 of Electronics Engineering Department, State Polytechnic of Malang, which consists of 44 students of experimental class and 44 students of control class. This study is designed by using quasi-experimental research designs (quasi -experiment) with the model design is Nonequivalent Pretest - Posttest Control Group Design. Based on data analysis, the results of the study (1) there are differences in learning outcome between groups of English speaking students taught by  learning strategy STAD with a group of students who are taught by conventional learning strategies (F = 45.970, p = 0.000), (2) there are differences in English speaking learning outcome between the students who have different learning modalities (F = 114.591, p = 0.000), and 3) there are interaction effect between learning strategy STAD and conventional and learning modalities (visual, auditory and kinesthetic) on English speaking learning outcome (F = 3.188, p = 0.044).